Mathematical model and calculation to predict the effect of prophylactic plasma transfusion on change in international normalized ratio in critically ill patients with coagulopathy. Issue 4 (31st December 2015) - Pham, Huy P.; Müller, Marcella C.; Williams, Lance A.; Juffermans, Nicole P.
Abstract : BACKGROUND: Plasma transfusion is often used prophylactically in patients with coagulopathy. However, the doses transfused may not be adequate to normalize hemostatic tests, which are commonly used as surrogate markers in practice. Currently, there is no reliable way to predict the posttransfusion international normalized ratio (INR) after plasma transfusion. Therefore, our aim was to develop and validate a formula that can reliably estimate post–plasma transfusion INR. STUDY DESIGN AND METHODS: A compartmental model was developed using demographic (sex, height, weight) and laboratory variables (hematocrit [Hct], INRinitial, and plasma volume transfused). The formula was validated using a data set from a multicenter trial conducted between May 2010 and June 2013 in critically ill, nonbleeding patients with coagulopathy, receiving prophylactic plasma transfusions. INR was measured just before and immediately after plasma transfusion. RESULTS: Initial plasma volume is calculated using the patient's Hct and blood volume (derived from Nadler's formula). The estimated immediate posttransfusion INR is then calculated as I N R p r e d i c t e d   =   I N R i n i t i a l − 0.9196 1 + β   +   β 0.8039 1 + β − 1.0874, w h e r e   β   =     P l a s m a   v o l u m e t r a n s f u s e d   P l a s m a   v o l u m e i n i t i a l . There was a significant agreement between the model predictions and the actual INR measurements after transfusion. A total of 83% of the predictions were within the acceptable range of variation. Furthermore, there was no proportional difference or systemic bias between the predictions and the actual INR measurements. CONCLUSION: This mathematical formula estimates posttransfusion INR after a certain volume of plasma transfusion with a good predictive ability. This formula, which only requires basic demographic and laboratory variables, may help the physicians to determine the volume of plasma required for a specific target INR in stable, nonbleeding patients.